Epidermal Growth Factor Receptor Down-Regulation Triggers Human Myoblast Differentiation - Leroy, Marina C. (Public Library of Science, 2013)
Initiation of human myoblast differentiation requires a negative shift (hyperpolarization) of the resting potential of myoblasts that depends on the activation of Kir2.1 potassium channels. These channels are regulated by a tyrosine phosphorylation. Using human primary myoblast culture, we investigated a possible role of various receptor tyrosine kinases in the induction of the differentiation process. We found that Epidermal Growth Factor Receptor (EGFR) is a key regulator of myoblast differentiation. EGFR activity is down-regulated during early human myoblast differentiation, and this event is required for normal differentiation to take place. Furthermore, EGFR silencing in proliferation conditions was able to trigger the differentiation program. This occurs through an increase of Kir2.1 channel activity that, via a rise of store-operated Ca(2+) entry, leads to the expression of myogenic transcription factors and muscle specific proteins (Myogenin, Myocyte Enhancer Factor 2 (MEF2), Myosin Heavy Chain (MyHC)). Finally, blocking myoblast cell cycle in proliferation conditions using a cdk4 inhibitor greatly decreased myoblast proliferation but was not able, on its own, to promote myoblast differentiation. Taken together, these results show that EGFR down-regulation is an early event that is required for the induction of myoblast differentiation.